(3GdaUhd GdegeI aj CUhd GdCFeIs - (3eMeO Hf GdMSf Hf Ydj GdYGedj , GdMQ GdYGedj,J (B1104 (3g` s ((3GHQGgje GdeSJgOi s)
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ Edi Gddg GdZfi eMeO Hf GdMSf Hf Ydi Hf eMeO Hf GdMSjf GdMQ GdYGedi s
(3BNQgG (B:s
(3deG eVi HcJ Ydjg GdSehGJ GdSHY hGdCQVhf GdSHY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B204s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B195s
Keywords: (3abg GdePGgH GdCNQis